2015
DOI: 10.1080/07391102.2014.999354
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of MG and pre-MG states of proteins by MD simulations, NMR, and other techniques

Abstract: Almost all proteins fold via a number of partially structured intermediates such as molten globule (MG) and pre-molten globule states. Understanding the structure of these intermediates at atomic level is often a challenge, as these states are observed under extreme conditions of pH, temperature, and chemical denaturants. Furthermore, several other processes such as chemical modification, site-directed mutagenesis (or point mutation), and cleavage of covalent bond of natural proteins often lead to MG like part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 209 publications
0
16
0
Order By: Relevance
“…Molecular dynamic (MD) simulations of chitinase provided a detailed information on the fluctuations and conformational changes . MD simulations can track system behavior and understanding of protein folding (Ubaid-Ullah et al 2014;Haque et al 2015;Naiyer et al 2015). These methods are used to investigate the structure, dynamics and thermodynamics of biological molecules (Anwer et al 2015;Hoda et al 2015;Naz et al 2015).…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…Molecular dynamic (MD) simulations of chitinase provided a detailed information on the fluctuations and conformational changes . MD simulations can track system behavior and understanding of protein folding (Ubaid-Ullah et al 2014;Haque et al 2015;Naiyer et al 2015). These methods are used to investigate the structure, dynamics and thermodynamics of biological molecules (Anwer et al 2015;Hoda et al 2015;Naz et al 2015).…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 99%
“…1B) monitored by  222 as a function of [urea], that at nearly 4.0-4.4 M concentration of urea, a stable conformation is achieved, which is more stable than native one (we named this state as X state), while at 6.0M HFE gets completely denatured (D state) ( Table 2) [46]. We found that secondary structure retained in X state, lies in the range 40-50% of that of N state, this implies that X state possess one of the structural characteristics of PMG state (the retention of near about 50% secondary structure of the native protein) [5,58].…”
Section: Discussionmentioning
confidence: 78%
“…ANS has low fluorescence in water and in the presence of compact folded proteins that do not allow the dye access to their hydrophobic interior, but becomes highly fluorescent when bound to molten globules that largely retain secondary structure but have a loose ternary conformation that allow access of the dye to the hydrophobic interior[24,25]. Conversion of a molten globule to a fully unfolded protein, however, reduces the fluorescence of ANS, likely because hydrophobic clusters are no longer present.…”
Section: Resultsmentioning
confidence: 99%